PENGARUH EFIKASI DIRI TERHADAP KESIAPAN KERJA SISWA KELAS XII PROGRAM KEAHLIAN OTOMATISASI TATA KELOLA PERKANTORAN - Seni Oktaviani, - (2021)
As an impact of global competition, the requirements to enter the working world have become increasingly higher. The high level of working requirements becomes a challenge for vocational high school education that is aimed at creating ready-to-work and confident graduates. This paper reports the results of research aimed to find about the effect of self-efficacy on work readiness of twelfth grade, vocational high school students. The research employed an explanatory survey method, where data were collected through a questionnaire that was distributed to 112 students. Data were analyzed using the descriptive analysis and inferential methods. The results of the descriptive analysis show that the variables of students' self-efficacy and work readiness were both in the medium category. Meanwhile, the inferential analysis results show that the variable of self-efficacy had a positive and significant impact on work readiness. Comprehensive efforts by teachers to improve students' self-efficacy are needed to facilitate students with knowledge and skills in accordance with the demands of the current working world and mentally prepare them to be ready for work.